Gypsum efflorescence on clay brick masonry: Analysis of potential efflorescence origins. (July 2020) - Janssen, Hans; Chwast, Jacek; Elsen, Jan
Gypsum efflorescence on clay brick masonry is a growing problem, leading to a persistent grey-white staining of masonry facades. Gypsum efflorescence has been reported in the United Kingdom, the Netherlands and Belgium, with a specific occurrence on masonry facades erected over the last few decades. This article investigates the origin of this recent occurrence of gypsum efflorescence, with accelerated testing of the gypsum efflorescence sensitivity of separate and combined masonry components. It is demonstrated that both brick and mortar may provide a gypsum source, respectively, via the dissolution of anhydrite and the carbonation of ettringite. Neither does however directly result in gypsum efflorescence, as the released gypsum commonly subfloresces below the brick surface. The efflorescence is instead triggered by mortar admixtures, the application of which has indeed risen strongly in recent decades. Avoiding gypsum efflorescence on clay brick masonry hence requires an inert alternative for the mortar admixtures.